Helping without English: Parental roles and realities in CLIL classrooms - Pratiwi, Febry Eka; Ifanka, Chindyana; Zahra, Tiara; Fitria, Risa (Accentia: Journal of English Language and Education, 2025)
This qualitative study explored the experiences of parents with limited English proficiency in supporting their children's education within Content and Language Integrated Learning (CLIL) settings. By conducting interviews with three parents whose children attended an English-medium elementary school in Indonesia, the study investigated how parents’ English proficiency influenced their involvement, the challenges they faced, the strategies they employed to overcome these barriers, and their suggestions for school support. The findings revealed key difficulties such as language barriers and limited ability to provide academic assistance. Even so, parents found ways to manage the challenges by adopting some strategies, such as private tutoring, translation tools, and encouraging their children to study more independently. The findings also showed that parental involvement in CLIL settings was influenced not only by language skills, but also by the effort parents put into supporting their children's motivation, independence, and academic success. This study highlights the crucial role of collaboration between schools and families, while also suggesting ways that schools can better support parents in multilingual learning settings. By presenting these insights, the study adds to existing discussions on bilingual and multilingual education and illustrates how parents take an active role in CLIL environments.